The replicability of oncolytic virus: Defining conditions in tumor virotherapy - Jianjun Paul Tian (Mathematical Biosciences and Engineering)
The replicability of an oncolytic virus is measured byits burst size. The burst size is the number of new viruses comingout from a lysis of an infected tumor cell. Some clinicalevidences show that the burst size of an oncolytic virus is a definingparameter for the success of virotherapy. This article analyzes a basic mathematical model that includes burst size for oncolyticvirotherapy. The analysis of the model shows that there are two threshold values of the burst size: below the first threshold, the tumor always grows to its maximum (carrying capacity) size; while passing this threshold, there is a locally stable positive equilibrium solution appearing through transcritical bifurcation; while at or above the second threshold, there exits one or three families of periodic solutions arising from Hopf bifurcations. The study suggests that the tumor load can drop to a undetectable level either during the oscillation or when the burst size is large enough.